The Aroids of the Matang Massif, Sarawak, Malaysian Borneo II : Kubah National Park - Peter C., Boyce; Wong S., Yeng (International Aroid Society Inc., 2008)
One trough, the cutting of the road continues to climb and then branches with the metalled part leading to the restricted rear of the telecommunications tower and an urmade part that leads up onto the plateau below the summit at c. 800 m (c. 2600 fit)...